Potential Analysis of Micro Hydro Power Utilizing Irrigation Canal Flow for Local Energy Autarky: A Case Study in Sumbergempol, East Java, Indonesia - Ulya Fakhrun Nisa', Rizqa; Thamrin, Suyono; Eko Saputro, Guntur (International Journal of Technology and Education Research, 2025)
Energy self-sufficiency (energy autarky) is an important issue in the development of sustainable energy systems, especially in rural areas that still depend on external energy networks. One renewable energy source that has not been optimally utilized is irrigation flow, which has a stable discharge throughout the year and can be converted into electrical energy through micro-hydro power plant (MHP) technology. This study was conducted to analyze the micro-hydro energy potential of irrigation channels in Sumbergempol District, Tulungagung Regency, as an effort to support local energy autarky. The research methods included direct flow rate measurements using the float method and area-velocity calculations, as well as manual head measurements. The measurement results showed a representative flow rate of 0.90-0.91 m³/s and an effective head of 0.80 m, resulting in a hydraulic power potential of 7.14 kW and an effective output power of approximately 4.28 kW. Based on the low-head characteristics, the most suitable turbine is the Archimedes Screw, with a recommended generator capacity of 6-7 kVA. Load requirement analysis shows that the micro-hydro power plant is capable of supplying approximately 3.16 kW for public street lighting, residents' homes, and mosque facilities. This study aims to provide a technical basis for the utilization of irrigation channels as an alternative energy source that supports increased energy access and local energy autarky in rural areas.